Quantification of L5 radiculopathy due to foraminal stenosis using three-dimensional magnetic resonance myelography - Kojima, Atsushi (Spine Surg Relat Res, 2017)
INTRODUCTION: This study aimed to evaluate morphological changes in the L5 nerve roots in control and symptomatic patients using magnetic resonance myelography [MRM]. Moreover, the utility of MRM for the diagnosis of intraforaminal or extraforaminal lesions in patients with L5 radiculopathy was evaluated using healthy subjects as controls. METHODS: Of 270 subjects who underwent MRM of the lumbar spine at our institution between April 2007 and December 2010, 135 patients (78 men and 57 women; average age: 61.3 years) with no history of spinal surgeries and nerve roots without infections, tumors, or malformations were selected for this study. The end-point measurements included the bifurcation angle of inclination (proximal tilting angle [PTA]) of the L5 nerve root as observed via MRM, lateral angle of inclination (lateral tilting angle [LTA]), bifurcation diameter (proximal nerve root width [PW]), and dorsal root ganglion (DRG) diameter (DRG width [DW]). DW ratio was then calculated for healthy controls and symptomatic subjects. We measured each parameter using the image information unification system ShadeQuest (Yokogawa, Tokyo, Japan). Two spinal surgeons conducted the magnetic resonance imaging evaluation. RESULTS: Swelling of the L5 DRG was detected in cases with intraforaminal or extraforaminal stenosis. With regard to the cutoff value of 6.5 mm for L5 DW, foraminal stenosis can be confirmed if DW is ≥6.5 mm or more via MRM. In cases where L5 DRG was swollen to ≥1.2 times the size in healthy subjects, L5 radiculopathy with foraminal lesions can be diagnosed. CONCLUSIONS: Our findings indicated that 3D MRM is a noninvasive technique and a useful tool for the diagnosis of intraforaminal or extraforaminal lesions in the lumbar spine. Therefore, it can be combined with other diagnostic methods used for the identification of intraforaminal or extraforaminal L5 nerve root lesion.